Web security in the finance sector: Analysing the security of financial web applications: A case study - Vieira, T.; Serrão, C. (2016 11th International Conference for Internet Technology and Secured Transactions (ICITST), 2016)
Nowadays, information security is an increasing concern in institutions and organizations. This concern is even greater in the finance sector, not only because the financial amount involved but also clients and organization’s private and sensitive information. As a way to test security in infrastructures, networks, deployed web applications and many other assets, organizations have been performing penetration testing (pentest) which simulates an attacker’s behavior in a controlled environment in order to identify its vulnerabilities. This article focusses on the analysis of the results of security audits conducted on several financial web applications from one institution with aid of automatic tools in order to assess their web applications security level. To help in security matters, many organizations build security frameworks for vulnerability assessment, security assessment, threat modeling, penetration testing, risk management and many more. As for penetration testing, organizations such as OWASP provide vulnerability and security information, a testing methodology, risk analysis and penetration testing tools.